Septopremaxillary ligament traction system: a review - Elayadath, Rajani R.; Palakunnu, Biswas P. (International Journal of Advances in Medicine, 2019)
Over the years, several animal studies have been conducted concerning the role of cartilaginous nasal septum, septopremaxillary ligament in midfacial growth. Most of the studies utilized non primate animal models at first and then more recently in primates such as chimpanzee. Proper choice of animal model to extrapolate from is critical for successful experimental design. Although nonhuman primates are phylogenetically closer to humans than other mammalian groups for better extrapolation to human condition, not all the craniofacial experiments require primate models. Renewed interests in understanding the influence of septopremaxillary ligament resection on midfacial growth led to many in vitro experiments on animal models. Recently systematic review of relevant animal experiment is regarded as a prerequisite for the conduct of the new clinical trials. Despite this fact, the literature addressing this topic in humans and systematic review on the effect of the septopremaxillary ligament is scarce. The more recent studies show that the maxillary labial frenum encloses the septopremaxillary ligament and forms an important constituent of septopremaxillary traction system. The biomechanical force mediating through the septopremaxillary ligament, maxillary labial frenum and nasolabial muscles results in stimulating their effects on sagital growth of the maxilla. The main purpose of this review is to update and extend the knowledge of the role of septopremaxillary traction system on the midfacial growth by synthesizing the available literature involving the septopremaxillary ligament resection in experimental models. If this review could synthesize the results of relevant research, a change in the therapeutic notions can also be expected.